SELF-DIRECTED FEEDBACK : An Attempt Towards Learner Autonomy In Writing - Akmilia, Tsara Desiana (2014)
This paper aimed to investigate the application of self-directed feedback in a writing classroom in terms of how it may affect their skills in writing and the students' response to it. The study was conducted in one of public high schools in Bandung, taking nine students of a science class as the participants. It employs a case study which is using interview and document analysis as the data collection techniques. The findings show that after the inclusion of self-directed feedback in four drafts, the students managed to have a progress in terms of organization, vocabulary, mechanics, and grammar in the process of writing a report text. The awareness of their own progress also indicates a trait of an autonomous learner. Most of the students saw self-directed feedback as a worthy technique to be used again in the subsequent lessons. As a conclusion, self-directed feedback is proven applicable in the writing classrooms as it functions as a step in making students acquire strategies of learning autonomy. For further research, it is suggested that self-directed feedback is included in a set of a self-monitoring strategy rather than one exclusive technique. Keywords: feedback, writing, learner autonomy ABSTRAK Penelitian ini bertujuan untuk menginvestigasi pengaplikasian self-directed feedback dalam kelas menulis dari segi sejauh mana hal ini dapat mempengaruhi keahlian siswa dalam menulis serta respon siswa terhadapnya. Penelitian ini dilaksanakan di salah satu SMA negeri di Bandung, dengan mengambil sembilan siswa dari kelas IPA sebagai partisipan. Penelitian ini menggunakan studi kasus yang melibatkan wawancara serta analisis dokumen sebagai teknik pengumpulan data. Temuan dari penelitian ini menunjukkan bahwa setelah diaplikasikannya self-directed feedback pada empat rancangan teks, kualitas siswa mengalami peningkatan dalam segi organisasi tulisan, pembendaharaan kata, mekanika tulisan, dan tata bahasa. Kesadaran siswa akan adanya kemajuan ini juga mengindikasikan salah satu ciri pembelajar mandiri. Sebagian besar siswa melihat self-directed feedback sebagai teknik yang penting untuk diaplikasikan kembali di pembelajaran selanjutnya. Dapat disimpulkan bahwa self-directed feedback telah terbukti dapat diaplikasikan di kelas menulis karena ia berfungsi sebagai salah satu langkah dalam menghasilkan siswa yang memiliki strategi belajar mandiri. Untuk penelitian selanjutnya, disarankan agar self-directed feedback diikutsertakan di dalam satu rangkaian strategi monitoring mandiri, bukan sebagai satu teknik yang eksklusif. Kata Kunci: Umpan balik, menulis, kemandirian belajar.